Writing Life : Suffering as a Poetic Strategy of Emily Dickinson. - Smith, Jadwiga (Jagiellonian University Press, 2012)
The analysis of a selection of Emily Dickinson's texts confirms the notion that suffering occupies the principal position in the poet's work. Her poetry constitutes an example of a painful literary quest for subjectivity as well as an act of self-transcendence, which means that through her writing the poet obtained conscious control over her personal anguish. By using pain as a poetic strategy she transformed her private biography into a literary text. In this way she became a model for coping with suffering and using it for self-examination and self-development.